2018
DOI: 10.6061/clinics/2018/e185
|View full text |Cite
|
Sign up to set email alerts
|

Increase of 10% in the Rate of Adverse Drug Reactions for Each Drug Administered in Hospitalized Patients

Abstract: OBJECTIVE:To assess the risk factors, incidence and severity of adverse drug reactions in in-patients.METHODS:This prospective study evaluated 472 patients treated at a teaching hospital in Brazil between 2010 and 2013 by five medical specialties: Internal Medicine, General Surgery, Geriatrics, Neurology, and Clinical Immunology and Allergy. The following variables were assessed: patient age, gender, comorbidities, family history of hypersensitivity, personal and family history of atopy, number of prescribed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
0
18
0
8
Order By: Relevance
“…In our study, the incidence rate of ADR occurrence was 2.73%, while in a most recently studies, it was reported from 8.7% to General system disorders 1 16.2%. 11,12 It might be because of wider population including children with a broad range of disorders, not only the cancer-developed patients. Additionally, females' population of this study was smaller than that of males (with the ratio of 0.54), which was approximately similar to several other studies, 4,13,14 as well as patients' mean age (6.656±0.442 years) that can be supported by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the incidence rate of ADR occurrence was 2.73%, while in a most recently studies, it was reported from 8.7% to General system disorders 1 16.2%. 11,12 It might be because of wider population including children with a broad range of disorders, not only the cancer-developed patients. Additionally, females' population of this study was smaller than that of males (with the ratio of 0.54), which was approximately similar to several other studies, 4,13,14 as well as patients' mean age (6.656±0.442 years) that can be supported by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are clinically relevant for medical decision making and selection of therapeutic strategy, especially as cumulative evidence implicates current anticancer therapy (chemotherapy and/or radiation therapy) in occurrence of ADR/Es in patients with cancer undergoing treatment. In fact, though limited, available data does indicate that approximately a tenth of the global population and up to a fifth (20%) of hospitalized patients experience ADR/Es [17,18], such as depression, loss of appetite, fatigue, disturbed sleep, cognitive difficulties, nausea, vomiting, and pain. Regardless of the unitary or clustered nature of these symptoms, they are associated with exacerbated QoL, with diminished physical, psychological, and social functioning.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 about 15% to 20% of ADRs relate to HDRs, which are actuated by presentation to a medication in a portion that is generally endured by solid people and the responses are classified by target side effects that can be multiplied after resulting re-introduction. 2 ADRs speak to an essential reason for dismalness and are thought to cause somewhere in the range of 10% and 30% of all healing center confirmations in more established patients. 3 In USA, over 90% of grown-ups matured multi-year and more seasoned utilize one prescription for every week and 10%-25% experience an antagonistic medication response.…”
Section: Types and Prevalence Of Adrsmentioning
confidence: 99%